Pendampingan Guru Matematika Menyusun Instrumen Penilaian Afektif dalam Pembelajaran Berbasis Kurikulum 2013 - Rohantizani; Erna Isfayani (LSM Catimore dan Sahabat, 2023)
The mathematics learning process in the 2013 Curriculum is focused not only on the cognitive and psychomotor domains, but also on the affective domain. The main problem is that the mathematics teacher at the Ummul Qura Masykur Elmuhsini Foundation school has difficulty in assessing the affective domains, such as religiosity, self-confidence, curiosity, responsibility, and others. The reason is that the teacher only conducts numerical assessments based on the results of paper and pencil tests and assesses the assessment only as a formality. Therefore, the ability of teachers to develop affective domain instruments in accordance with the 2013 Curriculum in learning mathematics is an important thing that must be trained. This community service aims to make it easier for mathematics teachers at the Ummul Qura Masykur Elmuhsini Foundation school to easily develop instruments on psychomotor, cognitive and affective based on the 2013 Curriculum. The stages of this training consist of preparation, implementation, and reflection. This training was attended by 10 mathematics teachers at the Ummul Qura Masykur Elmuhsini Foundation. The results of community service showed that the training was carried out well. The participants seemed excited and enthusiastic to ask questions during the training. Furthermore, the material taught in the training can be understood well by the participants.